Prarancangan Pabrik Etilen Glikol Dari Etilen Oksida Dengan Proses Dow Meteor Dan Desain Alat Utama Kolom Distilasi (Dc-101) - Rusdy, M. Isnaini Al; Sunarno, Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Monoethylene glycol (MEG) is a glycol compound with single bonds. MEG is used as an antifreeze in machinery, as a raw material for the production of polyethylene terephthalate, and as a heat exchange fluid. MEG production process is carried out by reacting the feed in the form of ethylene oxide with water and the obtained production capacity is 250,000 tons/year. The ethylene glycol production process is carried out through the Dow METEOR process which consists of 4 stages, those are the raw material preparation stage, the ethylene glycol formation stage, the ethylene glycol concentration stage, and the product separation stage. The main design is the distillation column DC-101, which is used to seperate monoethylene glycol from diethylene glycol and triethylene glycol as by-product. Based on the results of the economic feasibility analysis of the factory, the ethylene glycol plant is feasible to establish with a Payback Period (PBB) obtained of 2 years, an IRR of 22.738%, a Percent Return on Investment (ROI) is 30.59%, and a Break Event Point (BEP) is obtained by 60%.Keywords: Ethylene glycol,Ethylene Oxide, Dow METEOR, Distillation Column